Pursuit of environmental justice in urban forest planning and practice - Grant, Amber; Millward, Andrew A.; Edge, Sara (Frontiers in Sustainable Cities, 2023)
There is a growing demand for urban forest management that prioritizes genuine community involvement, acknowledges power imbalances within society, and embraces the principles of environmental justice. To assess current initiatives and share better/best approaches, examining how environmental justice principles are applied in urban forest planning and practice is crucial. This study aims to understand the perspectives of urban foresters on the factors that either facilitate or impede the attainment of environmental justice goals. Interviews were conducted with urban foresters from non-profit organizations and municipal government in San Francisco, California, and Seattle, Washington. The interviewees were asked to identify and discuss their tree planting and maintenance strategies, public engagement protocol, and inter-organizational collaboration processes. To provide a contextual understanding of environmental injustice in the study cities, the historical racist practice of neighborhood redlining was examined alongside current tree canopy cover, locations of environmental hazards, and the spatial distribution of persons of color and those living in poverty. The findings revealed that urban forestry professionals in each city approached environmental justice in distinct yet complementary ways: San Francisco prioritized distributional justice, while Seattle focused on elements of procedural and recognitional justice. The Race and Social Justice Initiative in Seattle and Proposition E in San Francisco have been instrumental in identifying and addressing inequities in urban forest planning and practice. Creating fair and inclusive urban forestry practices that prioritize disadvantaged neighborhoods has been a difficult task for both cities. Acknowledging and addressing past policies and cultural perspectives that have led to marginalization is crucial for building trust with these communities. Moving forward, prioritizing recognitional justice in urban forest planning and management should be a top priority.